Immobilization and stability studies of multi-thiol probes for electrical biosensors by label-free analysis. (2nd September 2017) - Kim, Won Jae; Shim, Min Suk; Chung, Minsub
ABSTRACT: For electrical biosensors based on gold electrodes, poor long-term stability of the monothiol-to-gold bonds has been a major issue for a robust and reliable performance of the sensor. The use of multi-thiol modified bioprobes was proposed to achieve a stable attachment. In this study, the binding kinetics and stability of mono/dithiol modified oligonucleotides were investigated using quartz crystal microbalance with dissipation (QCM-D) and electrochemical impedance spectroscopy (EIS). These label-free surface tools compared the binding, stability and the effect of dithiothreitol in solution of monothiol, dithiol, or disulfide modification. The potential for development of label-free, sensitive DNA microarrays is demonstrated.